2021
DOI: 10.1111/jocs.15787
|View full text |Cite
|
Sign up to set email alerts
|

Surgical redo mitral valve replacement in high‐risk patients: The real‐world experience

Abstract: Introduction Redo surgical mitral valve replacement (SMVR) remains the gold standard treatment in patients with a history of mitral valve surgery presenting with recurrent mitral valve pathologies. Whilst this procedure is demanding, it is an inevitable intervention for some indications, such as infective endocarditis, thrombosis, or multivalve procedures. In this study, we aim to evaluate our institutional experience with SMVR on a real‐life cohort, identifying the factors that contribute to poor surgical out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…We have read with great interest about Zubarevich et al's experience of surgical redo mitral valve replacement in high-risk patients. 1 We also congratulate the authors on the quality of their work, which provides a valuable experience about redo mitral valvuloplasty (MVP) in high-risk patients. They demonstrated with a retrospective study that the overall operative, 30-day, and 1-year mortality in the overall cohort were 3.4%, 22.4%, and 25.9%, respectively, and concluded that SMVR after prior mitral valve surgery presents a demanding procedure with high operative risk, significant mortality, and morbidity.…”
Section: To the Editormentioning
confidence: 98%
“…We have read with great interest about Zubarevich et al's experience of surgical redo mitral valve replacement in high-risk patients. 1 We also congratulate the authors on the quality of their work, which provides a valuable experience about redo mitral valvuloplasty (MVP) in high-risk patients. They demonstrated with a retrospective study that the overall operative, 30-day, and 1-year mortality in the overall cohort were 3.4%, 22.4%, and 25.9%, respectively, and concluded that SMVR after prior mitral valve surgery presents a demanding procedure with high operative risk, significant mortality, and morbidity.…”
Section: To the Editormentioning
confidence: 98%
“…Therefore, most patients referred for a redo surgery are older and present with multiple comorbidities. 2 With the rapid development of transcatheter mitral valve implantation especially in redo procedures, implantation of mechanical mitral valve prostheses is slowly losing its' popularity in western countries. 3 With the successful broad implementation of anti-infective treatment, rheumatic mitral valve disease has become highly uncommon in the western world.…”
Section: Mitral Valve Disease Rheumatic Heart Disease Redo Mitral Val...mentioning
confidence: 99%
“…The main causes of recurrent mitral valve disease in the western world are degeneration of biological valve prostheses, failed mitral valve repair, dysfunction of mechanical valve prostheses, and infective endocarditis. Therefore, most patients referred for a redo surgery are older and present with multiple comorbidities 2 . With the rapid development of transcatheter mitral valve implantation especially in redo procedures, implantation of mechanical mitral valve prostheses is slowly losing its' popularity in western countries 3 …”
mentioning
confidence: 99%
“…We read with great interest the article from Zubarevich et al 1 describing the risk factors for poor outcomes in high-risk patients undergoing mitral valve replacement (MVR). The authors identified NYHA class IV, infective endocarditis, postoperative dialysis, the high society of thoracic surgeons (STS) score, concomitant procedures, and mechanical prosthesis as risk factors for 30-day and 1-year mortality.…”
mentioning
confidence: 99%